Cult artifacts from the Neolithic and Chalcolithic settlement of Leceia, Oeiras, Portugal - Cardoso, João Luís (2013)
This study concerns 53 ideotechnic artifacts collected in the prehistoric settlement of Leceia, during a period of 20 years of excavations (1983-2002). They correspond to the most important group of artifacts found until now in Portugal due to their certified stratigraphic location in a vast fortified complex. The statuettes and other artifacts of cult character document the existence of religious practices from the second half of the 4th millennium BC through the second half of the 3rd millennium BC. Following the Late Neolithic zoomorphic representations, the Chalcolithic feminine images were related to fecundity, life and regeneration, corresponding to the omnipresent idol common to all agrarian societies of the Mediterranean basin. Images of this idol, represented in various shapes and materials, are found in domestic settlements and necropolises.